Early Invasive Cancer and Partial Intraoperative Electron Radiation Therapy of the Breast: Experience of the Jules Bordet Institute - C. Philippson; S. Simon; C. Vandekerkhove; D. Hertens; I. Veys; D. Noterman; F. De Neubourg; D. Larsimont; P. Bourgeois; P. Van Houtte; J. M. Nogaret (International Journal of Breast Cancer)
Objectives. The aim of this prospective phase II study is to evaluate the treatment of early-stage breast cancer (T1 N0) with intraoperative electron radiation therapy (IOERT) in terms of local control, early complications, and cosmesis. Patients and Methods. From February 2010 to February 2012, 200 patients underwent partial IOERT of the breast. Inclusion criteria were unifocal invasive ductal carcinoma, age ≥40 years, histological tumour size ≤20 mm, and no lymph node involvement. A 21 Gy dose was prescribed over the 90% isodose line in the tumour bed. Median follow-up is 23.3 months (7–37). Results. Acute toxicity was not frequent (Grade 1: 4.5%, Grade 2: 1%). The cosmetic result was considered to be very good or good in 92.5%. One ipsi lateral out-quadrant recurrence at 18 months was observed. The crude and actuarial local recurrence rates after median follow-up were 0.5% and 0.9%, respectively. Conclusion. The preoperative diagnostic work-up must be comprehensive and the selection process must be rigorous for this therapeutic approach reserved for small ductal unifocal cancers. After a 23.3-month median follow-up time, the clinical results of IOERT for selected patients are encouraging for the locoregional recurrence and the toxicity rates. The satisfaction of our patients in terms of quality of life was extremely high.